If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = x + (x + -20) Reorder the terms: 90 = x + (-20 + x) Remove parenthesis around (-20 + x) 90 = x + -20 + x Reorder the terms: 90 = -20 + x + x Combine like terms: x + x = 2x 90 = -20 + 2x Solving 90 = -20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 90 + -2x = -20 + 2x + -2x Combine like terms: 2x + -2x = 0 90 + -2x = -20 + 0 90 + -2x = -20 Add '-90' to each side of the equation. 90 + -90 + -2x = -20 + -90 Combine like terms: 90 + -90 = 0 0 + -2x = -20 + -90 -2x = -20 + -90 Combine like terms: -20 + -90 = -110 -2x = -110 Divide each side by '-2'. x = 55 Simplifying x = 55
| 37=2x-19 | | 3x+20-x=30 | | x+2.8=6.5 | | 110+3x-2=90 | | 4X-7=2(2X+7)-5 | | x/-3-5=3 | | 2X-7=2(2X+7)-5 | | y=16x+63 | | 240=0.5(x(30)) | | 16x^2+25-9=0 | | 2x+2(6x-9)=94 | | 14x+1=29 | | 8-7=2(2X+7)-5 | | sec(3x)=4 | | Y=100x-50 | | -2y-8=5y-1 | | 10x-13x+-5x=-15+8x | | 6x+3x-4=5 | | p/4-3=-2 | | 3n^2-25=-8 | | -6(1-x)=42 | | ln^(x)=(4/3) | | X-6+2x+3=90 | | -1-2x=-(-x+7) | | -5(3+4x)=65 | | 2(u+13)=86 | | 7(n-4)-6=-40+n | | 9x+8x-6x-5=6 | | 3x+11=-9-13 | | y=(x-1)(x+2)(x-4+3i) | | 10n^2+20n-76=4 | | 7*y/14=2 |